Assessing obstetrics perceived service quality at a public hospital - Martins, A.; Crespo de Carvalho, J.; Ramos, T.; Fael, J. (Procedia - Social and Behavioral Sciences, 2015)
Assessing service quality has become a major issue in the healthcare sector. Although direct evaluation has already taken place, literature is scarce in terms of the impact the distance covered by the user has on perceived service quality. The aim of this study was to assess the influence distance has on perceived service quality when no similar service alternatives are available. The Servperf instrument was used to collect data. All women who delivered babies in autumn 2011 were respondents to the questionnaire. Exploratory analysis was used to test research hypotheses. Cronbach’s alphas were computed to assess internal consistency. Findings show that Assurance is the quality dimension that contributes the most to patients’ perceived service quality and Tangibles is the one that contributes the least. It was also possible to conclude that the distance the patient has to cover to be served and its educational level influence patients’ perception of the service provided.